Determinants of Ebola Virus Disease Infection among Healthcare Workers, Montserrado County, Liberia - Shannon, F.Q. II (University of Ghana, 2016)
Background: Ebola Virus Disease (EVD) is a zoonotic and fatal illness. The fatality rates in outbreaks have ranged from 25% to 90%. An outbreak of EVD hit West Africa in 2014, especially Guinea, Liberia and Sierra Leone; claiming more than 2000 lives, including 881 health care workers. EVD caused about 378 cases and 192 deaths among healthcare workers in Liberia; Montserrado County was the hardest hit with over 90 cases and about 60 deaths. This research determined risk factors associated with Ebola Virus Disease infection among health workers in Montserrado County. Method: An unmatched case control study design was employed. It involved 168 participants (42 cases, and 126 controls). The study covered the period from May 2014 to May 2015. Cases (selected from health workers survivor database) included all healthcare workers reported as confirmed EVD cases in the Epi-surveillance and survivor database within the period of the outbreak. Controls included healthcare workers working (within the same one year period) in the same health facility or environment as the case subjects but did not have EVD. Self-administered questionnaires were employed. Data entry and analysis was conducted using Epi Info version 3.4.5. Result: Mean age of the study participants was 31.6 years (std. dev 7.1). The odds of being exposed to EVD in a health facility was 5.3 (CI 2.2-12.9) times higher in the cases compared to the controls. Maternity ward (OR 6.6, CI 2.1-21.0) and inpatient room/ward (OR 5.2, CI 1.9-14.1) were the places with the highest and significant odds of exposure to EVD in cases compared to their controls. Functions which had very high and significant odds of exposure among the cases compared to their controls included providing injection (OR 29.4, CI 3.5-243.4), placing intravascular device (OR 18.4, CI 4.9-68.7), providing medication (OR 16.9, CI 3.5-82.1), and emptying bedpan (OR 12.4, CI 2.5-62.4). Hand hygiene and wearing of Personal Protective Equipment (PPE) was relatively poor. Conclusion & Recommendations: Health care workers were at high risk for EVD infection during service provision especially when providing injection, placing intravascular device, providing medication, and emptying bed pan. Therefore, the need to address these risks and others cannot be overemphasized, as measures to prevent and manage future outbreaks and consequences that come along. Thus health authorities at all levels must ensure heightened vigilance and improved occupational safety measures, especially in the health facilities to prevent and manage EVD infection among health care workers.
Thesis(MPHIL)-University of Ghana, 2016
Keywords: Ebola Virus Disease Infection; Healthcare Workers; Liberia